Pengaruh Terpaan Bermain Boardgame Waroong Wars dan Tingkat Pendapatan Terhadap Minat Beli Kuliner Tradisional - Ahda Hanif Fauzi; Tandiyo Pradekso (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2020)
Boardgame currently continues to grow in Indonesia, as seen from the many local boardgame popping up and the player community itself. This is a potential that can be used by both governments and entrepreneurs in terms of promoting their products. And on the other hand Indonesia's per capita income continues to increase every year and its people eat at least once a day outside the home, still inferior when compared to neighboring countries, even though the increasing number of people dining outside can encourage economic growth through the culinary field. Thus this study aims to determine the effect of exposure to Waroong Wars board games and the level of income on buying interest in traditional culinary. Theories used in this research are Social Learning Theory and Information Consumption Theory. This research is a quantitative research with explanatory type. This study uses a non random technique with a total sample of 50 people aged 15 years and over who have played the Waroong Wars board game.. The results of a simple linear regression analysis show that exposure to playing Waroong Wars boardgame has no influence on traditional culinary buying intentions, indicated by a significance value of 0.101 which is greater than 0.05, and the level of income has no influence on traditional culinary buying interest. This can be seen from the test results obtained a significance value of 0.394 which is greater than 0.05. from the results obtained by exposure to playing the Waroong Wars board game and the level of income does not have an influence on buying interest in traditional culinary, it is recommended for culinary entrepreneurs to look for other alternative media to increase consumer interest in traditional culinary such as social media or food reviewers both in television media and Internet. As for the government, it is suggested to encourage the interest of buying traditional culinary through television and internet media as well as increasing the holding of traditional culinary festivals from various regions in Indonesia.